VISI GENDER PRODUK MAKANAN OLAHAN SUBSITUSI-DERIVATIF DAN MODA HEALING MASYARAKAT AQUATIK: Makanan Olahan Berbasis Ekosistem dan Moda Healing Aquatik, Kampung Dayun, Kecamatan Dayun, Kabupaten Siak - Yusmar Yusuf; Teguh Widodo; Risdayati Risdayati; Resdati Resdati; Robi Armilus; Syamsul Bahri (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Food security, stunting issues, hunger, and malnutrition are all interconnected with the theme of extreme poverty. This phenomenon has become a leading discourse in developing countries. On one hand, it is imperative that a country consciously designs agricultural ecosystems and food security frameworks. Communities living in aquatic environments are naturally connected to the tools and resources available within the broader ecosystem that has sustained and supported them for years. Their ability to adapt and even go beyond the “natural-normal” state, in processing raw materials found in their surroundings, reflects their effort to survive through the development of derivative food products. This community service program was conducted in the administrative region of Kampung Dayun, Siak Regency. The main objectives and functions include promoting the use of local natural resources as alternative processed food ingredients, ensuring the availability of abundant local food sources, and preparing food reserves. The activities carried out involved delivering public lectures, question-and-answer sessions, and practical training. These aimed to transfer knowledge and innovation to local communities and food product innovators. The focus was on processing non-rice food sources, such as cassava, corn, sweet potatoes, sago, taro, breadfruit, and other similar types. All of these food sources require extensive knowledge and creativity to be transformed into diverse food products.